2013
DOI: 10.1186/1471-2415-13-33
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of posterior vitreous detachment in a Chinese adult population: the Handan eye study

Abstract: BackgroundTo describe the prevalence and associations of posterior vitreous detachment (PVD) in a rural adult Chinese population.MethodsAll eligible subjects were requested to carry out a comprehensive eye examination; PVD was a pre-specified outcome variable and was determined via biomicroscopical examination (slit-lamp biomicroscopy) with a +90-D preset lens after mydriasis. Prevalence was standardized to China population census (2000).Results5890 (86.2%) subjects completed the examination of slit-lamp biomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…The prevalence of a complete PVD increases with age up to 28.1% at age 70-80 years; while prevalence estimates in the literature vary, primarily due to different examination methods, similar age relationships are reported (Weber-Krause & Eckardt 1997;Shen et al 2013). The population-based Handan Eye Study found a prevalence of 2.7% in Chinese subjects at age 30-70 years using funduscopy (Shen et al 2013). Weber- Krause & Eckardt (1997) reported an 11% complete PVD prevalence in 65-69-year-old subjects using kinetic sonography in a German cohort, increasing to over 45% in those over the age of 80 years.…”
Section: Discussionmentioning
confidence: 87%
“…The prevalence of a complete PVD increases with age up to 28.1% at age 70-80 years; while prevalence estimates in the literature vary, primarily due to different examination methods, similar age relationships are reported (Weber-Krause & Eckardt 1997;Shen et al 2013). The population-based Handan Eye Study found a prevalence of 2.7% in Chinese subjects at age 30-70 years using funduscopy (Shen et al 2013). Weber- Krause & Eckardt (1997) reported an 11% complete PVD prevalence in 65-69-year-old subjects using kinetic sonography in a German cohort, increasing to over 45% in those over the age of 80 years.…”
Section: Discussionmentioning
confidence: 87%
“…Other well-known VMI diseases such as macular hole and ERM have also been shown to occur more commonly with aging [16-18] and in women, [19-22] whereas there are inconsistent findings with regards to smoking as a risk factor. [11, 15, 23, 24] The reason that smoking is associated with VMA and VMT in AMD remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…10 The risk of PVD increases with age but high myopia can lead to an earlier onset of vitreous liquefaction. [10][11][12] Information on the prevalence of PVD in myopia is limited; however, prevalence was reported to be 12.5 per cent in a group of young adults with high myopia and was substantially high at 60.7 per cent in eyes with longer axial lengths, that is, axial length > 30 mm. 13 PVD can be visualised with the help of optical coherence tomography (OCT).…”
Section: Posterior Vitreous Detachmentmentioning
confidence: 99%